2020
DOI: 10.3389/fpls.2020.00563
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Magnesium Deficiency Triggers Nutrient Retranslocation in Arabidopsis thaliana

Abstract: Magnesium (Mg) is essential for many biological processes in plant cells, and its deficiency causes yield reduction in crop systems. Low Mg status reportedly affects photosynthesis, sucrose partitioning and biomass allocation. However, earlier physiological responses to Mg deficiency are scarcely described. Here, we report that Mg deficiency in Arabidopsis thaliana first modified the mineral profile in mature leaves within 1 or 2 days, then affected sucrose partitioning after 4 days, and net photosynthesis and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 86 publications
1
35
0
Order By: Relevance
“…In group V, genes involved in ubiquitin protein ligase binding were significantly down‐regulated at the translational level (Figure 3C). When compared with other published transcriptome data sets from samples subjected to Mg deficiency for various periods, we found that 18 of the 31 DEGs at the translational level (64.5%) were also transcriptionally regulated at least 5 d after treatment (Hermans et al, 2010a, 2010b; Ogura et al, 2020), and only two were regulated within 3 d after Mg deficiency. These results indicate that translation responses to Mg treatment are quicker and more sensitive.…”
Section: Resultsmentioning
confidence: 93%
See 4 more Smart Citations
“…In group V, genes involved in ubiquitin protein ligase binding were significantly down‐regulated at the translational level (Figure 3C). When compared with other published transcriptome data sets from samples subjected to Mg deficiency for various periods, we found that 18 of the 31 DEGs at the translational level (64.5%) were also transcriptionally regulated at least 5 d after treatment (Hermans et al, 2010a, 2010b; Ogura et al, 2020), and only two were regulated within 3 d after Mg deficiency. These results indicate that translation responses to Mg treatment are quicker and more sensitive.…”
Section: Resultsmentioning
confidence: 93%
“…There are 443 genes that are regulated by HY5 (Lee et al, 2007; Toledo‐Ortiz et al, 2014; Burko et al, 2020). After checking them against a list of published Mg deficiency responsive genes, including genes identified in this study, almost half of the 443 HY5 ‐regulated genes were regulated by Mg deficiency (Figure S6A; Hermans et al, 2010a, 2010b; Ogura et al, 2020). Among them, four chlorophyll synthesis‐related genes, Light‐Harvesting complex 4 ( LHCA4 ), Protochlorophyllide oxidoreductase ( PORC ), Genome uncoupled 5 ( GUN5 ), and Phytoene synthase ( PSY ), were down‐regulated at the transcriptional level by Mg deficiency treatment (Hermans et al, 2010b; Ogura et al, 2020), consistent with the previous report that HY5 regulates chlorophyll synthesis under dark/light transition and low/high temperature change (Toledo‐Ortiz et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations